INFECCIONES DE PROTESIS ARTICULARES - Quevedo Solidoro, Héctor (2024)
Total joint replacement is an important tberapeutic procedure but 1 % oí the cases are on risk oí secundary infection. We report two coxartrosis patients evaluated at the Navy Medica) Center who develop a prostetic Joint infection after a total joint replacement • . Doth patients were fema les aged 68 and 78 years respectively and tbe iníection occur after 9 days and 6 months after bes total jont replacement. In the first patient the source of the iníection was an adjacent soft tissue iníection and tbe microorganism isolate was Pseudomona aureginosa. In the Cormely Actinobacter bacteremia was the cause oí tite protesis iníection. We describe the clinical course of botb patients and discusse the causes oí joint iníection.